A kinematic analysis of ionized extraplanar gas in the spiral galaxies NGC 3982 and NGC 4152. Issue 2 (15th April 2021) - Li, Anqi; Marasco, Antonino; Fraternali, Filippo; Trager, Scott; Verheijen, Marc A W
ABSTRACT: We present a kinematic study of ionized extraplanar gas in two low-inclination late-type galaxies (NGC 3982 and NGC 4152) using integral field spectroscopy data from the DiskMass H α sample. We first isolate the extraplanar gas emission by masking the H α flux from the regularly rotating disc. The extraplanar gas emission is then modelled in the 3D position–velocity domain using a parametric model described by three structural and four kinematic parameters. Best-fitting values for the model are determined via a Bayesian MCMC approach. The reliability and accuracy of our modelling method are carefully determined via tests using mock data. We detect ionized extraplanar gas in both galaxies, with scale heights $0.83^{+0.27}_{-0.40}\, kpc$ (NGC 3982) and $1.87^{+0.43}_{-0.56}\, kpc$ (NGC 4152) and flux fraction between the extraplanar gas and the regularly rotating gas within the disc of 27 and 15 per cent, respectively, consistent with previous determinations in other systems. We find lagging rotation of the ionized extraplanar gas in both galaxies, with vertical rotational gradients $-22.24^{+6.60}_{-13.13} \, \mathrm{km\, s^{-1}\, kpc^{-1}}$ and $-11.18^{+3.49}_{-4.06}\, \mathrm{km\, s^{-1}\, kpc^{-1}}$, respectively, and weak evidence for vertical and radial inflow in both galaxies. The above results are similar to the kinematics of the neutral extraplanar gas found in several galaxies, though this is the first time that 3D kinematic modelling of ionized extraplanar gas has been carried out. Our results are broadly consistent with a galactic fountain origin combined with gas accretion. However, a dynamical model is required to better understand the formation of ionized extraplanar gas.